2009
DOI: 10.1007/s00542-009-0814-5
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of the film assembly of thermo-optic infrared focal plane arrays

Abstract: In order to improve the detection sensitivity of thermo-optic infrared focal plane arrays (TOFPA), we analyzed the optical characteristics of TOFPA and the influence of pairs of high/low index films (H/L, amorphous silicon and silicon nitride) with their extinction coefficients measured by spectroscopic ellipsometry. The results show that increasing the pairs initially increases and subsequently decreases the thermo-optic sensitivity of TOFPA because of the optical absorption of readout light, and slightly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…So the authorities such as University of california in Berkley (Varesi et al 1997;Mao et al 1999;Zhao and Mao 2002), Oak ridge national laboratory (Senesac et al 2003;Grbovic et al 2008); turkey (Ferhanoglu et al 2007), Boston University (huang et al 2008;Kwon et al 2009) and Shanghai Institute of Microsysytem and Information Technology, caS (Yan et al 2009) had concentrated on the research for about 7-10 years and also shown a lot of inspiring results. During 2007During -2013, we had also presented a novel Ir-FPa and successfully developed the model prototype of the infrared camera (Dong et al 2007;Jiao et al 2007;Yan-mei et al 2011).…”
mentioning
confidence: 97%
“…So the authorities such as University of california in Berkley (Varesi et al 1997;Mao et al 1999;Zhao and Mao 2002), Oak ridge national laboratory (Senesac et al 2003;Grbovic et al 2008); turkey (Ferhanoglu et al 2007), Boston University (huang et al 2008;Kwon et al 2009) and Shanghai Institute of Microsysytem and Information Technology, caS (Yan et al 2009) had concentrated on the research for about 7-10 years and also shown a lot of inspiring results. During 2007During -2013, we had also presented a novel Ir-FPa and successfully developed the model prototype of the infrared camera (Dong et al 2007;Jiao et al 2007;Yan-mei et al 2011).…”
mentioning
confidence: 97%